First synthesis of a noreremophilane isolated from the roots of ligularia przewalskii - Reddy, D. Srinivasa; Palani, K.; Balasubrahmanyam, D.; Kamath, V. B.; Iqbal, Javed (Tetrahedron Letters, 2005)
The total synthesis of a natural product noreremophilane has been achieved in just three steps from readily available starting materials. A highly stereo- and regio-selective Diels-Alder reaction was the key step in Our synthesis. (c) 2005 Elsevier Ltd. All rights reserved.

Novel pyrazole-3-carboxamide derivatives as cannabinoid-1 (CB1) antagonists: journey from non-polar to polar amides - Sasmal, Pradip K.; Reddy, D. Srinivasa; Talwar, Rashmi; Venkatesham, B.; Balasubrahmanyam, D.; Kannan, M.; Srinivas, P.; Kumar, K. Shiva; Devi, B. Neelima; Jadhav, Vikram P.; Khan, Sanjoy K.; Mohan, Priya; et al. (Bioorganic & Medicinal Chemistry Letters, 2011)
The synthesis and biological evaluation of novel pyrazole-3-carboxamide derivatives as CB1 antagonists are described. As a part of eastern amide SAR, various chemically diverse motifs were introduced. In general, a range of modifications were well tolerated. Several molecules with high polar surface area were also indentified as potent CB1 receptor antagonists. The in vivo proof of principle for weight loss is exemplified with a lead compound from this series. (C) 2010 Elsevier Ltd. All rights reserved.